2022
DOI: 10.5194/isprs-archives-xliii-b3-2022-855-2022
|View full text |Cite
|
Sign up to set email alerts
|

Uav-Based River Plastic Detection With a Multispectral Camera

Abstract: Abstract. Plastic is the third world’s most produced material by industry (after concrete and steel), but people recycle only 9% of plastic that they have used. The other parts are either burned or accumulated in landfills and in the environment, the latter being the cause of many serious consequences, in particular when considering a long-term scenario. A significant part the plastic waste is dispersed in the aquatic environment, having a dramatic impact on the aquatic flora and fauna. This motivated several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Wolf et al [68] developed APLASTIC-Q, a floating plastic litter identification, classification and quantification system using a machine learning algorithm based on convolutional neural networks, with an accuracy of 83% in identifying water, sand, vegetation and litter on beaches and within rivers in Cambodia. Cortesi et al [69] used an unmanned airborne multispectral camera to monitor floating litter in the Arno River, Italy, and used a stochastic Forest Machine Learning algorithm for litter identification, which showed an accuracy of more than 98% and concluded that the infrared band is helpful in improving the identification accuracy. Maharjan et al [70] processed UAV aerial imagery of the Mekong River tributaries-Huay Mai River and Bangkok Canal for deep learning and concluded that the various YOLO Deep Learning algorithms can all exceed 80% accuracy.…”
Section: Mobile Monitoringmentioning
confidence: 99%
“…Wolf et al [68] developed APLASTIC-Q, a floating plastic litter identification, classification and quantification system using a machine learning algorithm based on convolutional neural networks, with an accuracy of 83% in identifying water, sand, vegetation and litter on beaches and within rivers in Cambodia. Cortesi et al [69] used an unmanned airborne multispectral camera to monitor floating litter in the Arno River, Italy, and used a stochastic Forest Machine Learning algorithm for litter identification, which showed an accuracy of more than 98% and concluded that the infrared band is helpful in improving the identification accuracy. Maharjan et al [70] processed UAV aerial imagery of the Mekong River tributaries-Huay Mai River and Bangkok Canal for deep learning and concluded that the various YOLO Deep Learning algorithms can all exceed 80% accuracy.…”
Section: Mobile Monitoringmentioning
confidence: 99%
“…Environmental sciences use hyperspectral cameras mounted on a drone to detect plastic waste floating on the water surface [ 7 ]. Researchers present a system for the automatic detection of floating plastic waste based on a random forest classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Spectral angle mapping was used in [ 10 ] as well. Torti et al Cortesi et al [ 7 ] use a random-forest classifier to detect whether a given object floating on a river surface is plastic. Random forest, support vector machine classifiers, and a histogram-based gradient boosting classification tree are used to detect urban material such as asphalt, conglomerate, or sandstone [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, different tools and methods have been used over the years to detect and monitor floating plastic objects in fresh and salt water. Some researchers used in-situ visual census for their work (Galgani et al, 2013, Geraeds et al, 2019, but most used images or orthophotos obtained from satellite (Tasseron et al, 2021, Themistocleous et al, 2020, Topouzelis et al, 2020 or Unmanned Aerial Vehicle (UAV) imagery (Cortesi et al, 2022, Jakovljevic et al, 2020, Iordache et al, 2022, Cortesi et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
“…The use of drones allows not only great flexibility in planning time and location of the surveys but also a wide range of sensors is available, which can improve the overall plastic detection performance. In particular, (Cortesi et al, 2022) suggests that the combination of multi-spectral (in the range of EM wavelength from 433 to 875 nm) and thermal data could be used in order to reduce false positives. * Corresponding author…”
Section: Introductionmentioning
confidence: 99%